Arrhythpy: an automated tool to quantify and classify arrhythmias in Ca2+ transients of iPSC-cardiomyocytes - Ajmail, Karim; Brand, Charlotte; Borchert, Thomas; Meder, Benjamin; Rebs, Sabine; Streckfuss-Bomeke, Katrin (American journal of physiology. Heart and circulatory physiology, 2025)
Arrhythmias constitute an intricate and clinically significant phenomenon of great importance in various research areas. Calcium (Ca2+) homeostasis plays a pivotal role in forming rhythmic contractions in the heart, and its dysregulation has emerged as a critical component in the development of arrhythmias. However, the quantification of arrhythmias has been limited to indirect measurements via Ca2+ sparks, electrophysiological parameters, or manual classification, which can lead to human bias. We aimed to develop an analysis platform that automatically analyzes arrhythmias in human-induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs). Here, we present Arrhythpy, a robust and automated open-source program that quantifies and classifies confocal microscopy-based Fluo-4 Ca2+ transients to generate a measure of arrhythmia. In contrast to other automated and semiautomated analysis tools, which measure established parameters such as time-to-peak, Arrhythpy directly analyzes the degree of arrhythmia in a Ca2+ transient. We demonstrate its utility in monitoring Ca2+ transient-based arrhythmias in atrial and ventricular iPSC-CMs from healthy individuals and patients with cardiac disease, including dilated cardiomyopathy (DCM) and Takotsubo syndrome (TTS). Arrhythpy analysis of iPSC-CMs of patients with TTS recapitulated TTS phenotypes, including atrial arrhythmia that could be normalized with beta-blocker treatment. The program's adaptable framework enables the analysis of arrhythmic patterns in various cell types using periodic dye-based line scan measurement techniques, applicable to both single cells and layered cultures.